Where Do You Come from, where Do You Go? Assessing Skills Gaps and Labour Market Outcomes of Young Adults with Different Immigration Backgrounds - Alison Cathles; Dongshu Ou; Simone Sasso; Mary Setrana; Tom van Veen (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper analyzes numeracy and literacy skills of migrants, using PISA and PIAAC data from twelve OECD countries. Our results first show some convergence of the skills gap between the second generation immigrants and the natives over time. Second, the gap in literacy skills among the first-generation and natives and among first-generation and second-generation immigrants has increased over time. Third, demographics and family background contribute to the achievement gaps between different groups. Fourth, school input variables do contribute to skills gaps of young adults with different immigrant backgrounds. Fifth, an immigrant background does not appear to affect the chances of studying in a STEM field.
Keywords: I24; I25; 330